Philosophies of Sámi Education: Indigeneity, Place and Learning - Jannok Nutti, Ylva; Johansson, Viktor Magne; Schaffar, Birgit (Speki. Nordic Philosophy and Education Review, 2024)
The varied landscape of Sápmi – ranging from forests, coasts, mountains, tundra, and mires – and the livelihoods of those who live there have developed Sámi forms pedagogy, child-rearing, and education. This special issue explores the philosophies of Sámi education. The issue adopts a broad notion of education that involves formal and informal educational settings, kindergartens, schools and universities. Likewise, philosophy is understood widely as involving ethics, ontologies, epistemologies, and existential questions in theoretical investigations. Consequently, the aim is to take back education and philosophy that emerges from local indigenous practices, and various relations to land.